Relationship between Age, Parity, and Mother's Education with the Selection of 3 Months Injectable Family Planning in Banuayu Village, Lubuk Batang District, Ogan Komering Ulu Regency 2021 - Rini Anggelena; Syarifah Ismed; Helni Anggraini (Institute of Computer Science (IOCS), 2022)
Breadkground: Indonesia is a country with the fourth largest population in the world, so the government has launched the use of contraception. The most popular contraceptive is injection contraception by 34.3%. The purpose of the study was to determine the relationship between age, parity and education with the choice of 3-month injection KB in Banuayu Village, Lubuk Batang District, Ogan Ulu Regency in 2021. The research design was an analytical survey and a cross sectional approaches. The population in this study were all active family planning acceptors in Banuayu Village, Lubuk Batang District, OKU Regency and registered in the MCH/KB registration starting from January - July 2021 as many as 489 family planning acceptors who were still active and the number of samples was 83 respondents, 11 pill acceptors, 3 IUD acceptors, 12 natural family planning acceptors, 5 implant acceptors and 52 3 month family planning injection acceptors. The sampling technique used is systematic random sampling. The data collection tool is in the form of a check list. The data were processed univariately and bivariately by using the Chi-Square test with p value value (0.05). This research was conducted in August 2021. The results of the Chi Square statistical test stated that there was no significant relationship between age and the choice of 3-month injection KB with p-value = 0.756; there is no significant relationship between parity and the choice of 3-month injection KB with a p-value of 1,000; and there is a significant relationship between education and the choice of 3-month injection KB with a p-value of 0.004.